Cultural threat and perceived realistic group conflict as dual predictors of prejudice - Zárate, Michael A.; Garcia, Berenice; Garza, Azenett A.; Hitlan, Rbert T.
Recent research has focused on how perceived intergroup similarity influences stereotyping and prejudice. Very little is known, however, regarding how the quality or type of similarity influences intergroup relations. Presented is a methodology that allows one to manipulate the quality of perceived intergroup similarity. This methodology is used to test contrasting predictions about how perceptions of intergroup similarity on self-stereotyped interpersonal and work-related traits predict attitudes towards immigrants. Predictions were derived from cultural threat and perceived realistic group conflict theories. Some participants were asked to rate how similar they perceived their in-group was to Mexican immigrants, whereas others were asked to evaluate how the groups differed on the given traits. Control participants evaluated themselves on the given traits. Participants were presented with either interpersonal traits or work related traits as stimuli. The main dependent measures were a perceived realistic conflict scale, a prejudice scale, and a stereotyping scale. All three scales used Mexican immigrants as the target category. When interpersonal traits were made salient, contrast comparisons led to more negative attitudes towards immigrants, supporting a cultural threat hypothesis. When work-related traits were made salient, similarity comparisons led to more prejudice and more negative attitudes towards immigrants, supporting a perceived realistic conflict hypothesis. Thus, a perceived threat to either the cultural norm or economic well being led to more negative attitudes towards immigrants. Results are discussed for their relevance to models of intergroup relations.